SELECTIVE HYDROCRACKING OF HEAVY DISTILLATE TO HIGH VISCOSITY INDEX OF LUBE BASE STOCK USING BI-FUNCIONAL CATALYSTS - A.S. Nasution (Scientific Contributions Oil and Gas, 1991)
Selective hydrocracking of heavy distillate to high viscocity index of lube base stock has been carried out at the operating conditions: temperatures: 380Â° - 410Â°C, pressure: 100kg/cm2, H2/HC = 1000 lt/lt with bifunctional catalysts having various acidity using a catasest unit operated with a continuous system.